Pengembangan dan Pembaruan Manajemen Aplikasi pada Server - Agus Fatulloh; Alfatha Dhiki Alfatha Dhiki; Noranizah; Eka Wahyuni (Infoman's : Jurnal Ilmu-ilmu Manajemen dan Informatika, 2022)
In KomInfo Office, there is a Developer team that is tasked with developing applications. They save project on GitLab so that every member gets the latest. This project must also be stored on the server by Administrator. The Administrator must log in first to enter the server then pull the project files from GitLab and then save it on the server. This makes the project development process take longer, because it is necessary to develop a system that can connect GitLab and the server using the Microservices file on the server with the aim that the Administrator or Developer can directly save files to the server without need to log in repeatedly. The system development uses the spiral method so that in case of changes, additions, or system development can be done quickly according to the user's wishes. System testing is carried out using the black box method to ensure all functions are running normally. Measurement of the effectiveness of the system is carried out by survey and calculated using a Likert scale. As a result, this system was able to increase the effectiveness of work, especially those related to coordination, access, management, and speed of project completion.